Qualitative Research and Social Change
XI, 221 p.
Keywords: Exploring the relationships between qualitative research and social change, this bookasks how social change is informed and influenced by research. Examples discussed are from research practice and experiences in the fields of sociology, social work, professional practice, education, criminal justice and anthropology.".